Syariah court-annexed mediation in Malaysia: some problems and prospects - Abdul Hak, Nora; A. Oseni, Umar (Singapore Mediation Centre, 2011)
Islamic law considers any court-annexed framework for the resolution of disputes as part of the case management role of the judge. This paper examines the status of the cour-annexed mediation programme of the Syariah Court in Malaysia. Issues especially relating to the backlog of cases led to the introduction of sulf (mediation) as a court-annexed process with a review to acessing the problems, and their resolution. Overcoming these operational challenges identified will go along way in reducing the backlog of cases in the Syariah courts in Malaysia. A number of challenges are encountered in implementing this court annexed mediation.